TENDENCIES IN GREEN FINANCE - IULIA LUPU; ADINA CRISTE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
Green finance, a developing sector, started to attract more and more attention from the academic and practise perspectives. Awareness of environmental and climate change issues has highlighted finance's role. The development of this side of finance brings changes in the dynamics of financial markets, investors' behaviour, and the activity of regulation and supervision. The subject's topicality and importance reflect institutional funding orientation towards the green sector and climate change. These motivate our research on green finance topics, including a presentation on the dimension of green finance in the last years, the identification of the main characteristics of green finance in the specialized academic literature and the practice-oriented studies, and an overview of some aspects of the effects of the COVID-19 crisis on green finances